An Evaluation of Predatory Governance in Uganda and Indonesia - Fred Bidandi; John J. Williams; Jeremy Waiswa (Journal of Sociological Research, 2024)
The first part of this article theorises predatory governance in general and acmes some exceptions to the process. Subsequently, it reviews the characteristics of predatory governance literature in Africa and East Asia with emphasis on Uganda and Indonesia. The study shows how leaders utilise state resources and institutions for their self-interest and exclude the masses or tax payers who sustain such regimes. We show that, the extent to which regimes, influence policies on the general population politically or otherwise, creates inequality, poverty, unemployment, and bad governance. We, therefore, theorise that predatory governance is hinged on the idea that the state usually has limited capacity to protect citizen rights, the political and socio-economic spaces are usually controlled by the elites either through coercion, corruption or the use of violence. The impact of predatory governance and the developmental state as an approach for economic development has been discussed and we observe practical realities of vote-buying to win elections being a common practice in Uganda and Indonesia. In this understanding, both case scenarios portray an image of predatory behaviour. The study utilised secondary data to evaluate what predatory governance, its characteristics and impact. Findings show that predatory governance affects economic outcomes of a country, produces corruption, violence, nepotism, poverty, unemployment and shrinking democratic space and deficiencies to name but few.